Death of a salesman - Miller, Arthur 1915-2005 (Methuen Drama, 2022)
Why am I trying to become what I don't want to be ... when all I want is out there, waiting for me the minute I say I know who I am.Willy Loman is an ageing travelling salesman haunted, driven and yet held back by empty dreams of prosperity and success. Justly celebrated as one of the most famous dramatisations of the failure of the American Dream, the play's moral and political purpose is perfectly counterbalanced by a powerful and moving human drama of a man trying to make his way in the world and of the human flaws that lead to the shattering of his family and of their figurehead.Death of a Salesman is Miller's tragic masterpiece and considered one of the greatest plays of the twentieth century. Awarded the Pulitzer Prize in 1949, the play remains a classic work of literature and drama that is studied and performed around the world.This new edition includes an introduction by Claire Conceison that explores the play's production history as well as the dramatic, thematic, and academic debates that surround it; a must-have resource for any student exploring Death of a Salesman